2014
DOI: 10.7860/jcdr/2014/8350.4649
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Alkaline Phosphatase and Serum Phosphate as Predictors of Mortality after Stroke

Abstract: Context: Serum Alkaline phosphatase (ALP) & phosphate are considered to be indicators of vascular calcification. Link between bone metabolism, vascular calcification, cardiovascular events have been well studied in chronic kidney disease and ischemic heart disease.Aims: To determine that increased serum phosphate and alkaline phosphatase are predictors of mortality rates and recurrent vascular events in stroke. Materials and Methods:Sixty patients admitted with acute stroke (ischemic & haemorrhagic) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Several different mechanisms underlying the correlation of high serum ALP with poor functional outcome after ICH onset may be considered. First of all, ALP is often used as an early indicator of vascular calcification ( 15 , 30 , 31 ). Vascular calcification can further contribute to the process of atherosclerosis, which in turn results in vascular aging and increases the risk and extent of vessel rupture after stroke ( 7 , 11 , 16 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different mechanisms underlying the correlation of high serum ALP with poor functional outcome after ICH onset may be considered. First of all, ALP is often used as an early indicator of vascular calcification ( 15 , 30 , 31 ). Vascular calcification can further contribute to the process of atherosclerosis, which in turn results in vascular aging and increases the risk and extent of vessel rupture after stroke ( 7 , 11 , 16 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that elevated ALP was associated with all-cause mortality and subsequent cardiovascular disease in myocardial infarction survivors, clinic populations, and general populations (9). Moreover, it has been reported that ALP could predict mortality, functional outcome, and stroke recurrence, especially in those with ischemic stroke (11)(12)(13)(14)(15)(16)(17). However, the role of ALP on clinical outcomes of ICH patients has not been fully interpreted in previous studies conducted in a single center with relatively small cohort, and the underlying mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Prior clinical studies have explored AP as a diagnostic and prognostic marker to assess stroke risk by correlating indices of AP activity such as: dysfunctional bone metabolism (Barnadas et al 2014;Namba et al, 2017), cardiovascular disease (Webber et al 2010;Kim et al 2017;Makil et al 2017), cancer (Giessen et al 2014;Barnadas et al 2014;Hammerich et al 2017) and periodontitis (Kunjappu et al 2012). More importantly, elevated AP levels in stroke patients have been correlated with stroke severity and hypertension (Pratibha et al 2014;Tan et al 2017). While the underlying molecular mechanisms to support this association are unclear, other studies have provided additional support for this observation.…”
Section: Alkaline Phosphatase As a Diagnostic And Prognostic Stroke Biomarkermentioning
confidence: 94%
“…Clinical studies have shown that increased AP is associated with risk of cardiovascular disease, one of the many risk factors for stroke (Tonelli et al 2009;Park et al 2013;Wannamethee et al 2013;Kunutsor et al 2014). Elevated AP levels are correlated with more vascular deaths and recurrent vascular events, suggesting that AP may be a predictor for mortality in stroke patients (Pratibha et al 2014;Tan et al 2017). Abnormal AP has been associated with many of the risk factors leading to stroke, including heavy drinking (Ebuehi and Asonye 2007;Shimizu et al 2013a), obesity (Menahan et al 1985;Golik et al 1991), and hypertension (Shimizu et al 2013b).…”
Section: Alkaline Phosphatase As a Diagnostic And Prognostic Stroke Biomarkermentioning
confidence: 99%
See 1 more Smart Citation